Reading Albom's Tuesday with Morrie' to Enhance Students' Pedagogical Values in Literature Class for EFL Teacher Candidate (Universitas Negeri Semarang, 2022)
Enhanching pedagogical values for EFL teacher candidates is essential as this aggrandizement is aimed to support the students in teaching, educating and improving their professionalism. Moreover, because pedagogical values are values in social actions and interaction to strenghten both teachers and satudents relation in some different settings, it is a must to find means in exploring the values. One of them is a novel written by Mitch Albom entitled Tuesday with Morries. The novel is the main text in Literature Class for EFL teachers candidate. Hence, this research is aimed to describe the literature teaching process and to explore deeper the pedagogical values and teachers’ code ethics in this novel through close reading. Finally, the result; the cycle teaching in literature class, find the worldview, belief, and perspectives about teaching and learning in educational practices are found and used as tool to spread up values. Next, some practical pedagogy of Morrie Schwart as Mitch’s coach/lecturer were closely disscus. In addition, there were also precious values of life found from this novel.